Monoglyceride oleogels as fat replacers in filling creams for sandwich cookies - Palla, Camila Andrea (2020)
BACKGROUND: Many food products need to be reformulated to reduce the intake of saturated and trans fats which are considered unhealthy. In particular, the reformulation of filling creams (FCs) is challenging as these fats cannot be directly replaced with liquid oil without affecting the final product properties. This research studied the formulation and characterization of FCs for sandwich cookies using monoglyceride oleogel as fat material. RESULTS: FC formulated with 260 g kg−1 oleogel showed viscoelastic moduli values that did not differ significantly from those measured in a filling cream of commercial sandwich cookies (FC-CSCs) used as reference. The oil binding capacity of the FCs decreased with the increase of oleogel content. The increase of the oleogel amount in the formulation produced a decrease in hardness but an increase in adhesiveness and cohesiveness. Hardness, adhesiveness, and cohesiveness ranged from 0.66 to 3.48 N, 0.44 to 0.86 N s, and 0.07 to 0.29, respectively. When FCs were used for assembling cookies into sandwiches, an oil loss of about 9 g kg−1 FC after 21 days of storage was found in FCs containing 220 and 260 g kg−1 oleogel. The nutritional improvement due to the use of oleogel in FCs led to a reduction in saturated fatty acids between 64.5% and 35.2% and from 1.0 to 0.0% trans fatty acids in comparison with FC-CSC. CONCLUSION: Full fat replacement with monoglyceride oleogel in FC formulations allows the obtention of products with good quality and some similar characteristics to those obtained for FC-CSC, with the added benefit of a healthier nutritional profile. © 2020 Society of Chemical Industry.